(3CKQ HQfGeL JOQjHi dPhi UYhHGJ GdJYde Ydi GdJMUjd GdOQGSi dWdGH GdeQMdI GdKGfhjI HGdeYGgO GdCRgQjI (B/ s - (3SYjO CMeO SdjeGfs; (3ahbjI CMeO GdSjO YHOGdaJGM (B: s; (3efi MSf GdSjO (B: s ((3GdbGgQI (B: s (3SYjO CMeO SdjeGf (B: s, 2010)
(3JchfJ YjfI GdOQGSI ef (B(20) (3WGdH HGdUa GdKGfi GdKGfhi HeYgO KQhJ CHGXI HeOjfI GdRbGRjb Phi UYhHGJ JYde GdbQGAI ai GddZI GdaQfSjI Je JbSjege Edi eLehYJjf HGdJSGhi hPdc deYQaI CKQ GdHQfGeL GdJOQjHi Gdechf ef (B(25) (3LdSI HhGbY KdGK LdSGJ cd CSHhY ai GdJZdH Ydi gPg GdUYhHGJ hHGJHGY GdefgL GdJLQjHi hHGSJNOGe GdCSGdjH GdEMUGFjI GdefGSHI GNJjGQ hjdchcShf hGNJHGQ eGf hjJfi CKHJJ GdfJGFL CKQ GdHQfGeL ai GdJZdH Ydi UYhHGJ GdbQGAI ai GddZI GdaQfSjI dWdGH GdeQMdI GdKGfhjI HGdCRgQs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ hGdHMhK GdJQHhjI (B- (3bSe GdGQTGO GdfaSi hGdJQHhis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJMUjd GdOQGSis; (3UYhHGJ GdJYdes; (3UYhHGJ GdbQGAI s